2018
DOI: 10.1136/bmjopen-2018-022406
|View full text |Cite
|
Sign up to set email alerts
|

Design of a treatment pathway for insomnia in prison settings in England: a modified Delphi study

Abstract: ObjectiveInsomnia is highly prevalent in prisoners and is a risk factor for poor mental well-being, depression, suicidality and aggression, all common concerns in this vulnerable population. Improving sleep management options in prison offers the potential to impact positively on a number of these common risk factors. The study aim was to design a treatment pathway for insomnia in prisons informed by stakeholders with professional or lived experience of insomnia and prison-based interventions.DesignA modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…(15) Given the suffering, health risks, and other consequences associated with sleep deprivation, clinicians have a responsibility to evaluate and treat incarcerated patients with sleeprelated concerns, including underlying conditions that may be contributory. Institutional treatment pathways can support decision making in these scenarios (20). Some evidence suggests that nonpharmacologic strategies, such as relaxation techniques or brief cognitive-behavioral therapy, may help mitigate the effects of incarceration on sleep, and turning to these strategies before pharmacotherapy may be useful for treating insomnia in correctional settings (1,3,20).…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(15) Given the suffering, health risks, and other consequences associated with sleep deprivation, clinicians have a responsibility to evaluate and treat incarcerated patients with sleeprelated concerns, including underlying conditions that may be contributory. Institutional treatment pathways can support decision making in these scenarios (20). Some evidence suggests that nonpharmacologic strategies, such as relaxation techniques or brief cognitive-behavioral therapy, may help mitigate the effects of incarceration on sleep, and turning to these strategies before pharmacotherapy may be useful for treating insomnia in correctional settings (1,3,20).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Institutional treatment pathways can support decision making in these scenarios (20). Some evidence suggests that nonpharmacologic strategies, such as relaxation techniques or brief cognitive-behavioral therapy, may help mitigate the effects of incarceration on sleep, and turning to these strategies before pharmacotherapy may be useful for treating insomnia in correctional settings (1,3,20). Careful review of insomnia-related medication prescribing patterns, analysis of patient outcomes, and use of evidence-based formulary restrictions are also key for supporting patient wellbeing (16).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Poor sleep quality, often referred to as "sleep disturbance", is found in up to 55% of the elderly population and consistently increases with age population experiences insomnia at some point in their lives; however, recent figures show prisoners are at least twice as likely to have insomnia and the majorities have poor sleep quality [7]. This is problematic because insomnia has been shown to significantly contribute to poor cognitive functioning, depression, suicide, emotional deregulation, aggression and lack of treatment engagement, all of which may affect the safe running of the prison, an individual's rehabilitation and, ultimately, the likelihood of reoffending [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, poor sleep hygiene, including daytime naps, boredom or paucity of daytime activity, is evident in prisoners [11]. Availing sleep management options in prison offers the potential to impact positively on a number of these common risk factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies showed that, during imprisonment, inmates are much more likely to develop sleep disturbances in general, or more specifically, insomnia [42,43]. In this context, the high prevalence of depressive symptoms in prisoners [25,44], in addition to both a high level of anxiety and the prison's environment, could explain the poor sleep quality and the insomnia symptoms.…”
Section: Introductionmentioning
confidence: 99%